Peningkatan Kepedulian Mahasiswa Terhadap Kebersihan Pantai Melalui Aksi Bersih Pantai - Fitriansyah, Ahmad; Arisandi, Debby (Jurnal Pemberdayaan Komunitas MH Thamrin, 2019)
Batam is one of the largest islands in the Riau Islands and as an island the outer border of Batam is a coastal area. As an archipelago city, then start the tour in the city of Batam, further from marine tourists. The existing marine tourism objects are beach tourism, which is still largely managed by the community self-help. The management of these self-tourism causes the existing attractions tend to be poorly maintained, especially the problem of cleanliness. Based on data from the Batam City Tourism Office consisting of 19 coastal tourism areas managed by the community. Tourist attractions to help people manage beach tourism. Activities carried out by the methods that are directly involved in saving the beach environment and submitting to the community to ask for cleanliness and processing waste on the beach. The activity was carried out on April, 15, 2018, in the coastal area of the Malay village of Batu Besar, Nongsa District, Batam City. The results of the activity consisted of 56 participants consisting of three lecturers, 17 students and 26 community members of the Batam Beach Clean Up Community (BBC)